2020
DOI: 10.1017/jfm.2020.660
|View full text |Cite
|
Sign up to set email alerts
|

Wave scattering by an array of metamaterial cylinders

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 38 publications
4
37
0
Order By: Relevance
“…The model of Marangos & Porter [4] applies to close spacing between the plates where tensor elements are expressed explicitly in terms of the distances from the surface to the top of the array of plates and to the base of the fluid. This model arises from homogenization which exploits the contrast in the lengthscales in the problem and is adopted from Porter [6] and Zheng et al [7]. In these two problems, the plate arrays extend throughout the fluid depth allowing the exact depth dependence of the fluid to be factorized from the solution without depth averaging and is therefore not restricted to long wavelengths.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The model of Marangos & Porter [4] applies to close spacing between the plates where tensor elements are expressed explicitly in terms of the distances from the surface to the top of the array of plates and to the base of the fluid. This model arises from homogenization which exploits the contrast in the lengthscales in the problem and is adopted from Porter [6] and Zheng et al [7]. In these two problems, the plate arrays extend throughout the fluid depth allowing the exact depth dependence of the fluid to be factorized from the solution without depth averaging and is therefore not restricted to long wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst Porter's [6] work concentrated on refraction across planar interfaces, Zheng et al [7] considered the effect on waves of plate arrays confined within a circular cylinder. The small gaps between the plates provide an environment for resonance and slow wave propagation across the cylinder giving it the ability to concentrate wave energy which can either be harnessed/dissipated via a local damping mechanism or redirected to create a water wave lensing device.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Garnaud & Mei (2009) have previously shown that a compact array of floating buoys extracting power in heave and distributed over a circular region of the surface can absorb more than the equivalent size of a rigid cylinder. Zheng, Porter & Greaves (2020) have demonstrated how a structured porous cylinder can be capable of exceeding the equivalent rigid-body absorption limits. Very recently, Michele et al.…”
Section: Introductionmentioning
confidence: 99%